Hybrid Vehicle Adoption – A Conceptual Study - Soon, Wong Lai; ., Wong Kee Luen; ., Jenny Marisa Lim Dao Siang (Journal of Education and Vocational Research, 2013)
Market share of hybrid vehicle is still low as compared to non-hybrid vehicle. From business point of view, slow growth in hybrid vehicle sales may causes losses on hybrid automobile manufacturers and they may end up withdraw from the market. In order to increase the sales of hybrid vehicle, a solution must be generated. To find a good solution, automobile producers must understand the market condition as well as the reasons/factors that influenced adoption of hybrid vehicle. This research aims to contribute to the understanding on the consumer behavior that causes the adoption of hybrid vehicle and hope to contribute to the reduction in global warming as well as theoretical development.